Biohydrogen production from palm oil mill effluent under thermophilic condition using suspended and immobilised mixed cultures - Ismail, Isnazunita (2011)
Dark fermentation is light independent bioconversion of organic materials by anaerobes to biohydrogen (biolf-), carbon dioxide and organic acids. Despite the successes achieved in biohydrogen production from simple sugars and carbohydrate rich wastewater, there are still limitations in the practical application of this process to complex substrate such as palm oil mill effluent (POME). In industrial application, the potential of readily available inoculums such as methane digester sludge has to be evaluated for biohydrogen production. Understanding the main chemical constituents either carbohydrates, protein or oil in POME that renders biohydrogen production will provide insight on the potential energy recovery in the form of hydrogen from POME. Continuous fermentation will be a step forward to determine the stability of biohydrogen production system from POME. This thesis specifically investigates the potential of producing biohydrogen via continuous fermentation in a completely stirred tank reactor (CSTR) system using POME as feedstock under thermophilic (55°C) condition. Two different cells systems were evaluated separately; using suspended cells and immobilised cells entrapped in polyorganosiloxane polymer. Sludge from methane digester for treatment of POME was initially tested for its suitability as biohydrogen-producing inoculum under batch fermentation. Sludge pre-treated with hydrochloric acid at pH 3 for 24 hr and later pH reinstated to working pH of 5.5 was compared with the untreated sludge in batch experiments using synthetic medium-containing (5 g/L) glucose. Acid pre-treatment was part of attempt to suppress growth of hydrogen-consuming methanogens. The untreated sludge exhibited high specific hydrogen production rate (HPR) of 460 mL/g VSS/d as compared to the acid-treated sludge (135 mLig VSS/d). Controlling the pH of fermentation at 5.5 suffices in eliminating methane generation and renders biohydrogen production without the requirement to pre-treat the suspended mixed cultures. The untreated sludge was then used for subsequent studies related to suspended cells system. Another batch fermentation study was conducted to determine the fate of carbohydrate and oil that are presence in POME using model substrates; sucrose and crude palm oil. The kinetic profile indicated that mainly sucrose was metabolised by the mixed cultures with biohydrogen yield of 2.5 mol H2/mol heXOSe_addeHde.nce for subsequent POME fermentation, the hydrogen yield was monitored solely on unit volume of hydrogen produced per gram of carbohydrate consumed. Continuous fermentative biohydrogen production was carried out over a period of 60 to 150 days for evaluating the system stability. The suspended cells system showed better performance than the polydimethysiloxane-immobilised cells system with biohydrogen yield of 1.72 and 1.58 mol H2/mol POME-hexose, respectively at hydraulic retention time (HRT) of 4 days. The corresponding hydrogen production rate (HPR) was 2.6 ± 0.9 NL H21L POME/d with biohydrogen constituted up to 52% of the total biogas. The denaturing gradient gel electrophoresis (DGGE) profile of effluent samples showed increasing strong band of dominant hydrogen-producing bacteria species phylogenetically related to Clostridaceae at reduced HRTs, which also explained washout of these bacteria from the bioreactor. However, only 13% of the total organic contents of POME was utilised in the fermentation with potential energy yield of 2.4 MJ/kg COD consumed. These have render POME unfavourable as feedstock for recovering more biohydrogen energy under current operating conditions.